Impact of ambient wind on aerodynamic performance when two trains intersect inside a tunnel. Issue 169 (October 2017) - Chen, Zhengwei; Liu, Tanghong; Zhou, Xisai; Niu, Jiqiang
Abstract: In this study, the aerodynamic performance of two trains that intersect inside a tunnel under ambient wind conditions is investigated. A full-scale test is conducted to verify the computational method and mesh, and then a series of numerical simulations are performed to investigate the pressure variation and the aerodynamic force coefficient by comparing with the condition of no ambient air. The difference between the results with/without ambient wind in a tunnel is analysed. The results indicate that if Train A travels downwind, the positive pressure of train surface increases and the negative pressure decreases as the wind velocity increases, and the arrival time of the maximum positive pressure lags on average 0.024 s and 0.058 s for wind velocities of 20 m/s and 40 m/s, respectively. For the tunnel wall measuring points, the maximum positive pressure increases as the wind velocity increases. The maximum drag coefficient of downwind Train A decreases by 4.7% and 10.1% for wind velocities of 20 m/s and 40 m/s, respectively, whereas that of upwind Train B increases by 5.7% and 15.8%, respectively. The maximum positive side force coefficient of downwind Train A increases by 20.8% for an ambient wind velocity of 40 m/s, whereas the same coefficient decreases by 16.7% for upwind Train B. Highlights: The aerodynamic performance of two trains intersect in a tunnel under ambient wind conditions is investigated. A waveform increase or decrease characteristic inside a tunnel for the train surface is analysed. Train runs downwind, the arrival time of the maximum positive pressure lags. For the tunnel wall measuring points, the maximum positive pressure increases with an increase in wind velocity. The side force coefficient of train runs downwind increases and decreases for train runs upwind.